Linguistic Metamorphoses of the Kievan Caves Paterikon - Temčinas, Sergejus (Senoji Lietuvos literatūra, 2024)
The article presents a general overview of the known linguistic versions of the Kievan Caves Paterikon, and concludes that the chronology of their origin does not correspond to the general line in the development of the linguistic situation in the East Slavic lands of the Lithuanian-Polish Commonwealth. The information presented below about two unknown Ruthenian translations of the Paterikon significantly changes the overall picture, which, after taking them into account, becomes much more logical and chronologically consistent. Each of the two Ruthenian versions newly introduced into scientific circulation is characterized in terms of its textual volume and the composition of the Paterikon stories contained in it, and the sources used for its creation.